O processo de trabalho em ambulatorio de saude mental - Bertoncello, Neide Marina Feijó [UNESP]; Da Silva, Graciette Borges (My University, 1998)
This study was carried out to evaluate the working procedures of the mental health at the medical and administrative team at the mental health outpatient unit in Botucatu, attempting to understand its previous and social characteristics in relation to psychiatry, health and Brazilian society. The objective of this study was to analyze the activities being used and the professional inter-relationship of the team. It tried to identify the main factors that controlled the actions, the social needs are attended to. Direct observation and interviews focused on the patients and workers were the methods used. The results were reviewed in the lights of the concepts of 'work technological organization' and 'working process' which enabled the identification of the units of work at the center. After all, it was noticed that there were two distinct trends of work organization: one of them aimed at individual treatment by medical staff and the other aimed at group treatment by non-medical staff.
The working procedures in a mental health outpatient unit
Keywords: Mental health; Outpatient unit; Working process; Brazil; doctor patient relation; medical staff; mental health care; outpatient care; social aspect; teamwork